Lifestyle and Consumers’ Choice of Laundry Services in Manado City: An Empirical Study - Jenny N. Kaligis (International Journal of Applied Business and International Management, 2020)
Lifestyle, including activities, interests, and opinions, influences consumer shopping behaviour and decisions in laundry businesses. It relates to individual’s way of life, use of money and time, expressed in activities, interests, and opinions. Therefore, those partaking in this business need to understand their consumers’ lifestyle, for complete information on what products to offer, innovate, and promote. This study was conducted in Malalayang, Paal 2, Boulevard, and the areas surrounding Sam Ratulangi Airport, the central areas of modern laundry businesses in Manado. The findings suggest that lifestyle simultaneously conferred a positive and significant effect on consumer’s laundry service preference. Therefore, every related dimension, including activities, interests, and opinions, also significantly affects the parameter under investigation.